PENGARUH INOVASI PRODUK DAN KUALITAS PRODUK TERHADAP KEPUASAN PELANGGAN PADA PRODUK WARUNG RAJA SEBLAK WAHYU - yesika Tamba; Maria vinci lumbantoruan; Laurena Ginting; Vina Gabriella saragih (STKIP Subang, 2026)
The culinary business is one of the business sectors experiencing rapid growth in Indonesia, with seblak buffet being one of the products that is widely favored by people from various circles. The purpose of this study is to examine the effect of product innovation and product quality on the level of customer satisfaction at Warung Raja Seblak Wahyu in Medan City. The research approach used is descriptive quantitative with a survey method of 50 respondents who were randomly selected using a random sampling technique, so that each customer has an equal opportunity to be a research sample. The results of the analysis show that product innovation and product quality have a positive and significant effect on customer satisfaction, indicated by the Adjusted R2 value of 0.762. Separately, product innovation shows a positive but insignificant effect with a Sig. 0.169 > 0.05, while product quality has a positive and significant effect. The results of this study confirm that product quality is the most dominant factor in increasing customer satisfaction compared to product innovation